PELATIHAN PENGEMBANGAN MEDIA AJAR BERBASIS CANVA DAN WORDWALL - Hadi, Sunandar Azma'ul; Jauhari, Ade (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
Training on developing teaching materials based on Canva and Wordwall has been carried out with very satisfactory results. This training is designed to improve teachers' skills in using both platforms effectively. Canva, as a graphic design tool, makes it easy to create attractive visual teaching materials such as posters and infographics, while Wordwall allows the creation of interactive educational activities, including web-based games and quizzes. During the training, participants experienced obstacles related to the differences in the types of accounts used, namely free accounts versus Pro accounts, which limit access to some premium features. However, suggestions to upgrade to a Pro account at an affordable cost were expressed to maximize the benefits obtained. The combination of Canva and Wordwall in developing teaching media offers an innovative approach that increases student engagement and facilitates more dynamic learning. In-depth discussions during the training showed the enthusiasm of the participants and the desire to overcome problems such as decreased student motivation. This training is expected to have a significant positive impact by helping teachers create teaching media that are more interactive and in accordance with student needs, thereby improving the classroom atmosphere and the effectiveness of the learning process